Inflammasome targeting for periodontitis prevention is sex dependent - Tomaz Alves; Karen V. Swanson; Mustafa S. Girnary; Marcelo Freire; Kevin Moss; Kimon Divaris; James Beck; Pollyana Coelho Pessoa Santos; W. June Brickey; John A. Wrobel; Heidi Yeigi Min; Manaal Syed; et al. (Proceedings of the National Academy of Sciences, 2025)
Inflammasome initiates inflammation via the maturation of interleukin-1 beta (IL-1β). Periodontitis is a prevalent, male-biased disease characterized by inflammation-driven bone loss, yet the mechanism(s) of this sex bias is unknown. This study explored whether enhanced inflammasome represents a causal mechanism for this bias. Analyses of three separate human studies (>6,200 samples) show that males have significantly higher IL-1β in the gingival crevicular fluid than females during health and periodontitis. This pattern is experimentally reproduced with different versions of the ligature-induced periodontitis mouse model where males show greater IL-1β secretion than females. The inflammasome drives bone resorption in males but not females as revealed by analyses of inflammasome gene-deletion mice. Pharmacologic treatment with a caspase-1/4 inhibitor reduces inflammatory cell infiltration, dampens osteoclastogenesis signaling (via the receptor activator of nuclear factor-kappa B pathway), and prevents bone resorption in males but not females during experimental periodontitis. While ovariectomized females show no change in their nonresponsiveness to caspase-1/4 inhibition, orchiectomized males no longer respond to the inhibition, suggesting the importance of an intact male reproductive system in the mediation of this inhibition. Thus, our study identifies inflammasome activation as causal for male-biased experimental periodontitis and supports sex-stratified studies to foster future advancement of inflammasome therapeutics in periodontics.